Resistance prediction of solar boat in calm water using computational fluid dynamic approach / Muhamad Daniel Haiqal Md Izaninulhadi - Md Izaninulhadi, Muhamad Daniel Haiqal (2022)
The issue that are that solar boat are very power limited than conversional boat. It is because the boat itself run with a rechargeable battery that can only be charge using the solar in the daytime. Analysis of its swath hull is very important for solar boat to have a more travel distance. Solar boat usually had a catamaran hull, but this experiment will use swath as hull for the solar boat. Analyze swath is quite difficult since it similar like catamaran but a little bit difference since it torpedoes need to be underwater because of this the boat will have a big drag. It makes solar boat to have very limited travel distance. Computational fluid dynamic “CFD” need to be use properly since analyze resistance of swath hull itself could make boat designer the it designs so it can fix it design to be more efficient and effective to be use for the solar boat.